Analisa Kelayakan Sistem Pentanahan Area Wokrshop Plant PT. Saptaindra Sejati Job Site Boro - Fauzan Iqbal; Sitti Amalia; Zuriman Anthony; Zulkarnaini Zulkarnaini (Journal on Education, 2023)
Workshop is the sole construction project owned by PT. Saptaindra Sejati Job Site Boro. There are 4 newly constructed workshops that each have unique functions. With a roof area of somewhat more than 720 m2 and a height of 20 meters. The most important bangunan in the business's area is the workshop. This raises a number of risks, the most significant of which is bangunan tersambar petir since sifat petir dominan menyambar tempat tertinggi. Approximately 7 computers crashed after the petir sambaran. Where the computer in question contains important company data. Without any analysis or corrective action, this situation could result in operational deterioration and reduce a company's profit. In the year 2021, PT. Saptaindra Sejati Job Site Boro certified a kelayakan system pentanahan. The goal of the certification was to understand kelayakan bangunan prior to use and to obtain a certificate from KTT (Kepala Teknik Tambang) PT. Borneo Indobara. The results of the previous system certification for the building's workshop were good and clearly stated. However, uji kelayakan ulang system pentanahan bangunan dan penangkal petir workshop did not yet take place in 2022. According to Pemerintah Uji regulations, pentanahan is carried out every two years, while, according to PUIL, every six months. It was determined through analysis and testing that the voltages for sentuh and long-wave tegangan with a frequency of 0.5 seconds each had been determined to be within acceptable standards, i.e., 173,891 and 155,371 Volt, respectively. As a result, it was possible to state that the pentanahan system in the workshop area was functioning properly.